Translation and Validation of Italian Version of Index of Dental Anxiety and Fear (IDAF-4C+): A Cross-Sectional Study - Stefano Salgarello; Maria Luisa Garo; Corrado Paganelli; Antonio Vita; Matteo Salvadori; Elisabetta Audino (MDPI AG, 2021)
Dental anxiety (DA) is defined as unreasonable apprehension toward dental procedures. About 4-20% of the worldwide adult population presents DA, with peaks of 30% in the younger population. Managing patients with dental anxiety and fear with a reliable and valid instrument is necessary to understand the multidimensional dimensions of dental fear. This work aimed to validate the Index of Dental Anxiety and Fear (IDAF-4C+) into Italian. Two hundred and eighty dental students attending an Italian university were enrolled. The IDAF-4C+ was translated by experts and a native English translator, blinded to the original version. The Modified Dental Anxiety Scale (MDAS) was used to assess the validity of IDAF-4C+. Spearman correlation coefficients and Exploratory Factorial Analysis (EFA) were used. Reliability was evaluated by Cronbach's alpha. The reliability of the Italian version of IDAF-4C+ was good (Cronbach's alpha = 0.88). Correlation between IDAF-4C+ and MDAS ranged between 0.42 to 0.68. From EFA, one factor explained 58.76% of the common variance. Women showed a higher level of dental fear. The Italian IDAF-4C+ is a valid and reliable tool to assess DA in any clinical context. This instrument allows for a proper understanding and management of DA, and therefore a better patient oral health-related quality of life and compliance with the dentist's instructions.